Effect of immune status on dengue 2 virus replication in cultured leukocytes from infants and children. - Marchette, N J (1979)
Cord blood leukocytes from neonates with maternal dengue antibody supported dengue 2 virus replication in vitro; those from neonates without maternal antibody did not. Cord bloods of infants born to dengue-immune mothers contained a potent enhancing factor which gradually decayed with age and which was absent from neonates born to nonimmune mothers. Permissiveness of cultures of washed peripheral blood leukocytes from infants with maternal antibody declined steadily with increasing age in parallel with the decay of maternal antibody, and the leukocytes were no longer permissive after 10 to 12 months. The demonstration of a dengue maternal infection-enhancing factor in human cord blood from dengue-immune mothers supports the hypothesis that severe primary dengue hemorrhagic fever with shock seen in Bangkok infants is related to maternal immune status.